Fenomen kreacyjny pogranicza: efekty pograniczności w biografiach twórczych, historii i geografii literatury - Margreta Grigorova (Postscriptum Polonistyczne)
The article discusses Polish borderlands as a creative phenomenon. It considers their cultural and historical importance and the research that has been conducted from 1940 till today. The author uses the term „borderland“ (pogranicze) as defined by T. Bujnicki (Mechanizmy funkcjowania pogranicza kulturowego, 2006). The author explains how borderlands create important cultural situations, significant phenomena and she also proves the borderland character of Polish culture (C. Miłosz, Polskie kontrasty, 1995; Rodzinna Europa,2001; S. Bereś, Historia literatury polskiej w rozmowach, 2002).